Helping the helpless: contribution of rural extension services to smallholder farmers' climate change adaptive capacity and adaptation in rural Ghana - Asare-Nuamah P, Botchway E. and Onumah J.A. (International Journal of Rural Management)
While there is no doubt that extension services play an active role in promoting smallholder farmers$1 (Badaptive capacity and adaptation to climate change, there is a dearth of information and research on how this institution champions climate change adaptation in rural farming communities in Ghana. This study employed a qualitative case study design and interviewed 15 extension officers and 26 smallholder farmers to understand how extension services enhance smallholder farmers$1 (Bclimate change adaptive capacity and adaptation in the rural Adansi North District in Ghana. The findings indicate that extension services adopt multiple strategies to build the adaptive capacity of farmers to climate change. Through the transfer of skills and knowledge, technology and innovations, supply of inputs, technical advice and liaison role with existing local institutions, farmers are able to adapt to climate change. The study further revealed that extension services are hindered by geographical, sociocultural and economic challenges which affect their alignment and fitness to effectively assist smallholder farmers. The study recommends strengthening the capacity of the extension institution. Moreover, more experts must be trained to provide special, targeted and important services to smallholder farmers in respect of climate change sensitization and adaptation.- Reproduced s
Keywords: Extension services, Climate change, Smallholder farmers, Adaptation, Adaptive capacity, Ghana